The denomination of origin product markets through fair trade. Perspectives and challenges (2018)
This document aims to highlight how products with the distinctive denomination of origin can benefit when they are placed on the market under fair trade practices. It is concluded that fair trade, as a commercial model, can constitute an alternative to contribute to the protection of products with denomination of origin; however, there are several challenges to achieving its implementation. © 2018, Universidad Nacional Autonoma de Mexico. All rights reserved.